2016
DOI: 10.1371/journal.pgen.1006129
|View full text |Cite
|
Sign up to set email alerts
|

Misregulation of Alternative Splicing in a Mouse Model of Rett Syndrome

Abstract: Mutations in the human MECP2 gene cause Rett syndrome (RTT), a severe neurodevelopmental disorder that predominantly affects girls. Despite decades of work, the molecular function of MeCP2 is not fully understood. Here we report a systematic identification of MeCP2-interacting proteins in the mouse brain. In addition to transcription regulators, we found that MeCP2 physically interacts with several modulators of RNA splicing, including LEDGF and DHX9. These interactions are disrupted by RTT causing mutations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 68 publications
6
59
0
Order By: Relevance
“…Therefore, a tight regulation of the ratios of different alternatively spliced isoforms is highly important for proper functioning of the neuronal networks. Indeed, aberrant ratios between the flip and flop isoforms of the Gria1-4 subunits of AMPAR have been linked recently to abnormal synaptic transmission in RTT (12). Our study showed widespread aberrations in alternative splicing, specifically in response to neuronal activity in RTT mice.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, a tight regulation of the ratios of different alternatively spliced isoforms is highly important for proper functioning of the neuronal networks. Indeed, aberrant ratios between the flip and flop isoforms of the Gria1-4 subunits of AMPAR have been linked recently to abnormal synaptic transmission in RTT (12). Our study showed widespread aberrations in alternative splicing, specifically in response to neuronal activity in RTT mice.…”
Section: Discussionsupporting
confidence: 53%
“…This conundrum has led to other studies, some of which have suggested that MeCP2 is not a gene-specific transcriptional repressor but rather a global repressor that abundantly binds methylated DNA and dampens transcriptional noise genomewide (6), that MeCP2 acts as both a repressor and an activator (5,7,8), that MeCP2 functions in a celltype-specific manner (9,10), and that MeCP2 is a long-gene-specific repressor (4). Other studies have suggested that MeCP2 functions posttranscriptionally as a regulator of alternative splicing (11,12), or as a regulator of microRNA expression (13)(14)(15). Although these studies advanced our understanding of the function of MeCP2, they also clearly emphasize that the molecular mechanism which mediates RTT is likely complex and has yet to be deciphered.…”
mentioning
confidence: 99%
“…Neuron-specific isoform expression is essential to proper cell-type specification as shown from recent studies in neuronal development (Furlanis and Scheiffele, 2018;Saito et al, 2019;Schwartzentruber et al, 2018), disease (Gandal et al, 2018;de la Torre-Ubieta et al, 2016;Parikshak et al, 2016;Voineagu et al, 2011) and activity Parikshak et al, 2016;Quesnel-Vallières et al, 2016). While many neurological diseases, including autism (Quesnel-Vallières et al, 2016;Voineagu et al, 2011), Rett syndrome (Cheng et al, 2017;Kriaucionis and Bird, 2004;Li et al, 2016), Huntington's disease (Lin et al, 1993;Sathasivam et al, 2013;Wood, 2013), spinal muscular atrophy (Cartegni et al, 2006;Lorson et al, 1999;Parente and Corti, 2018;Xiong et al, 2015) and schizophrenia (Gandal et al, 2018;Glatt et al, 2011;Morikawa and Manabe, 2010;Nakata et al, 2009;Wu et al, 2012) have been linked to disruptions in alternative splicing, this mechanism of gene regulation is understudied in the context of drug abuse and addiction. Only one study thus far has reported that investigator administered cocaine results in greater changes in isoform expression than gene expression in the NAc (Feng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing is a key mechanism for gene regulation in brain. Aberrant splicing is implicated in myriad neurological diseases, such as autism (Gonatopoulos-Pournatzis et al, 2018;Quesnel-Vallières et al, 2016;Voineagu et al, 2011), Rett syndrome (Cheng et al, 2017;Kriaucionis and Bird, 2004;Li et al, 2016), Huntington's disease (Lin et al, 1993;Sathasivam et al, 2013;Wood, 2013), spinal muscular atrophy (Cartegni et al, 2006;Lorson et al, 1999;Parente and Corti, 2018;Xiong et al, 2015) and schizophrenia (Gandal et al, 2018;Glatt et al, 2011;Morikawa and Manabe, 2010;Nakata et al, 2009;Wu et al, 2012). However, this mechanism of gene regulation is understudied in neuropsychiatric diseases, including drug addiction.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously constructed engineering splicing factors (ESFs) by fusing functional domains of known splicing factors to an RBD with programmable specificity (PUF domain from human PUM1). The resulting ESFs have been successfully used in manipulating AS of endogenous genes in cultured cells and model animals (Li et al, 2016;Wang et al, 2009). Additionally, this strategy also provides a convenient and standard system to assess the function of splicing regulatory domains.…”
Section: Introductionmentioning
confidence: 99%